Socialism without liberation: Land Reclamation Projects in Guinea-Bissau - Dirk Kohnert (Sociologia Ruralis, 1988)
One of the outstanding aims of most liberation movements has been to increase the economic well-being of their people, Guinea-Bissau being no exception in this respect. How far has the new Nation State succeeded in fulfilling this aim? A comparative analysis of the implementation of land reclamation projects during colonial and post-colonial times reveals astonishing similarities: especially the centralization of development efforts in the hands of administrators disconnected from the grassroots, lack of target group analysis and misconceptions about the aims and needs, as well as the resources, of the population involved in the development efforts, on the part of the administration. The effects of this negative conditioning process of 'development' over many years on the chances of cooperation between peasants and the administration are still largely unknown. Any development planner who wants to encourage the local population to take their future into their own hands, would have to take account of this negative conditioning process. – – Socialisme sans libération: Projets de réhabilitation des terres en Guinée-Bissau: Un des objectifs exceptionnelle de la plupart des mouvements de libération a été d'accroître le bien-être économique de leur peuple. La Guinée-Bissau ne fait pas exception à cet égard. Dans quelle mesure le nouvel État Nation réussi à remplir cet objectif? Une analyse comparative de la mise en valeur des projets de réhabilitation des terres pendant la période coloniale et post-coloniale révèle des similitudes étonnantes: notamment la centralisation des efforts de développement dans les mains des administrateurs déconnectés de la base, le manque d'analyse du groupe cible et des idées fausses sur les objectifs et les besoins, ainsi que les ressources, de la population impliquée dans les efforts de développement, de la part de l'administration. Les effets de ce processus de conditionnement négatif du «développement» depuis de nombreuses années sur les chances de la coopération entre les paysans et l'administration sont encore largement inconnu. Tout planificateur du développement qui veut encourager la population locale à prendre leur avenir en mains propres, devra tenir compte de ce processus de conditionnement négatif.
Additional information: Author's version
Keywords: P2; P51; P32; O12; Z1; Z13; A14; 330; Democratization; Land use systems; Guinea-Bissau; Africa; Colonialism; African Socialism; Demokratisierung; Landnutzung; Feuchtgebiet; Reisanbau; Guinea-Bissau; Subsahara-Afrika; Afrikanischer Sozialismus; Kolonialismus